Administration of Probiotics in Recirculating System Cultivation to Improve the Health of Colossoma macropomum - Sinaga, Nurilam; Riauwaty, Morina; Lukistyowati, Iesje (Jurusan Budidaya Perairan, Fakultas Perikanan dan Kelautan, Universitas Riau, 2024)
Probiotic containing Nitrosomonas sp and Nitrobacter sp play a role in the nitrification process to improve water quality in the media maintenance. This research was conducted in July – October 2021 at the Laboratory of Fish Parasites and Diseases, Faculty of Fisheries and Marine, Riau University. The purpose of this study was to obtain the best dose of Kp Super N probiotics for fish health. The method used is an experimental method using a one-factor with five treatment levels and three replications. The treatments applied were Cn (maintenance without probiotic Kp Super N and without being challenged with Aeromonas hydrophila), Cp (maintenance without probiotic Kp Super N and challenged with A. hydrophila), maintenance was given probiotic Kp Super N and challenged with A. hydrophila: P1 (2 mL/80 L of water), P2 (3 mL/80 L), P3 (4 mL/80 L). Fish were reared for 72 days. The results shown that the best treatment was P3 (4 mL/80 L) with a total erythrocyte of 2,70 x 106 cells/mm3, haematocrit value of 36,00%, and hemoglobin level of 8,17 g/dl, total leukocytes 8,17 x104 cells/mm3, leukocrite 3,17%, lymphocytes 63,00%, monocytes 4,00%, neutrophils 1,00%, and platelets 32,00%. Weight growth was 23,29 g and the survival rate 100%. The water quality temperature 26 – 29,7oC, pH 6 – 7,5, DO 4,9 – 5,2 ppm, ammonia 0,05430-0,00062 mg/L, nitrite 0,0549-0,1709 mg/L, and nitrate 0,2000-3,6670 mg/L. Based on the date obtain, it can be concluded that the probiotic Kp Super N is able to improve the health of Colossoma macropomum